A new host of Trypanosoma cruzi from Jujuy, Argentina: Octodontomys gliroides (Gervais & D'Orbigny, 1844) (Rodentia, Octodontidae). - Schweigmann, N.J. (1992)
To identify wild hosts of Trypanosoma cruzi, surveys were conducted in the subandean valleys of Jujuy Province, Argentina, between June 1986 and March 1987. Seventy two mammals from 13 different species were examined by xenodiagnosis. Fifty two of them were mostly rodents trapped at the localities of Maimará, León and Tilcara, and the remainder had been kept in captivity at the Estación Biológica Experimental, in Jujuy. Trypanosoma cruzi infection was detected only in 2 Octodontomys gliroides (2 pos./8 exam. 25%) from all 72 examined mammals. Isolates were called Octodontomys Argentina 1 and 2 (OA1 and OA2). Both infected animals were caught at the archaelogical ruin of Pucará, at Tilcara. Repeated searches for triatomines in the ruin itself and in neighbour houses rendered negative results. Groups of mice inoculated with either OA1 or OA2 isolates became infected between 7 (OA1) to 12 days (OA2) postinoculation PI. Parasitemia peaks were observed between day 12th-14th PI. Scarce amastigote nests were found in myocardium and skeletal muscle. Mortality was observed only for mice inoculated with OA1. Isoenzyme patterns of OA1 and OA2 were identical to one found in dogs and slightly different from that of human parasites in Argentina. Bones from Octodontomys sp., were recently found in a cave, dated 10200-8600 BC, in Pumamarca, near Tilcara, Jujuy. There are evidences that O. gliroides cohabited with man in ancient times and was associated to the domestic cycle of T. cruzi transmission, playing a role like that of domestic caves in Bolivia.